2021
DOI: 10.1021/acsnano.1c05790
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Magnetic Anisotropy in van der Waals Ferromagnet-based Heterostructures

Abstract: Interface engineering is an effective approach to tune the magnetic properties of van der Waals (vdW) magnets and their heterostructures. The prerequisites for the practical utilization of vdW magnets and heterostructures are a quantitative analysis of their magnetic anisotropy and the ability to modulate their interfacial properties, which have been challenging to achieve with conventional methods. Here we characterize the magnetic anisotropy of Fe3GeTe2 layers by employing the magnetometric technique based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Deng et al used an ionic gate to raise the Curie temperature (Tc) of trilayer FGT to room temperature, which is much higher than the bulk Tc. According to the topics covered by most studies focused on fundamental magnetic physics and spintronic devices, FGT as a candidate will have promising applications in the next generation of Opto-electromagnetic information science and technology. However, high-quality FGT single crystal to date has been generally synthesized with a small quantity, which greatly limits the in-depth property research and potential applications.…”
Section: Introductionmentioning
confidence: 55%
“…Deng et al used an ionic gate to raise the Curie temperature (Tc) of trilayer FGT to room temperature, which is much higher than the bulk Tc. According to the topics covered by most studies focused on fundamental magnetic physics and spintronic devices, FGT as a candidate will have promising applications in the next generation of Opto-electromagnetic information science and technology. However, high-quality FGT single crystal to date has been generally synthesized with a small quantity, which greatly limits the in-depth property research and potential applications.…”
Section: Introductionmentioning
confidence: 55%
“…However, the insufficiency of a stable mass production technology and integrated intrinsic nature development is usually a huge obstacle that restricts the in-depth research and applications of emerging materials. Currently, the typical preparation methods of 2D FGT are mechanical exfoliation , and molecular beam epitaxy. For example, an FGT nanodevice was made by repeatedly exfoliating FGT crystals via Scotch tape and then carefully transferred to pretreated electrodes after attaching to a PDMS stamper . Liu et al obtained a 2D FGT film under a vacuum of 2.5 × 10 –9 Torr through a molecular beam epitaxy system equipped with a crystal oscillator and in situ reflection high energy electron diffraction system.…”
Section: Introductionmentioning
confidence: 99%
“…22 Deng et al 40 increased the T C of mechanically exfoliated atomically thin FGT to room temperature through an ionic gate, much higher than that of bulk crystals. Kim et al 33 showed that the interfacial vdW materials (h-BN, WSe 2 ) on FGT can locally tune the perpendicular magnetic anisotropy of heterostructure systems, leading to multiple magnetic behaviors in a single channel. However, the insufficiency of a stable mass production technology and integrated intrinsic nature development is usually a huge obstacle that restricts the in-depth research and applications of emerging materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations